Nonlinear Adaptive Barrier Integral Super Twisting Sliding Mode Control of Hybrid Energy Systems in Ship DC Microgrid: Modelling, Management, and Experimental Validation - Hamza Mahmood (329043); Dr. Hassan Abdullah Khalid (Islamabad : USPCAS-E, NUST, 2024)
TH-582
Keywords: MS EEP Thesis; MS Thesis